Enhancing data collection methods with qualitative projective techniques in the exploration of a university's brand identity and brand image. (March 2021) - Spry, Louise; Pich, Christopher
This article focuses on assessing the capabilities of projective techniques, in gaining a deeper insight into complex university corporate brands. In particular, we will explore identities and how these might align with brand images in different departments and faculties. There are explicit calls for further research on projective techniques in new contexts in particular, and where and when they are most useful during data collection. Responding to this gap in the literature, this study adopts a two-staged approach to the research design utilizing qualitative projective techniques as a supplement to more traditional methods of data collection. This article provides an updated matrix on how qualitative projective techniques can be better utilized during the planning, research, and analysis stages of research in different contexts. This can be employed to assist inexperienced and experienced individuals with projective techniques during the planning, research, and analysis stages of research into corporate brands.